Electronic and Adsorption Properties of Furfural and Hydrogen on Cobalt Alumina Surfaces: A DFT Study - Abdullah, Nooraihan; Ahmad, Amierah Rasyeedah; Istiqomah, Elida Lailiya; Mohd Khazali, Khairul Anwar; Saad, Shakila; Jamil, Siti Jasmida; Wan Jaafar, Wan Nurhadani (Semarak International Journal of Electronic System Engineering, 2025)
This study reports a density functional theory (DFT) investigation that extends prior Co/Al₂O₃ and furfural studies by analysing their combined interface. Furfural is selected as a representative oxygenated molecule derived from biomass to examine the fundamental interaction mechanisms on transition-metal–oxide interfaces. The research was conducted to understand how cobalt atoms and the alumina support contribute to adsorption stability, charge redistribution, and hydrogen activation at the atomic level. Although cobalt–alumina catalysts are widely used in biomass conversion, the fundamental physics governing adsorption and charge redistribution at the metal–oxide interface remain unclear. Previous studies have focused mainly on catalytic performance, leaving the atomic-level mechanisms insufficiently understood. The calculations were performed using density functional theory to optimize the Co/Al₂O₃ surface and evaluate adsorption configurations, charge-density differences, and projected densities of states. Several adsorption structures of furfural were analyzed to identify the most stable configuration, and hydrogen adsorption and dissociation were examined to locate the active sites on the surface. The carbonyl oxygen of furfural bonds strongly with cobalt atoms, with an adsorption energy of about 1.3 eV. A charge transfer of around 0.2 electrons occurs from cobalt to furfural, showing strong orbital interaction near the Fermi level. Hydrogen molecules adsorb weakly on the surface but dissociate easily on cobalt sites, with an activation barrier of about 0.8 eV. Cobalt acts as the main active site for hydrogen splitting, while alumina plays only a minor role. Overall, cobalt atoms provide stable binding sites for oxygenated molecules and promote hydrogen activation, both of which are essential for high catalytic performance. The findings provide a detailed physical description of adsorption and electron transfer behaviour that explains the catalytic activity of cobalt– alumina surfaces and contribute to a better understanding of surface-mediated processes relevant to biomass conversion and energy materials.